AMPA Receptor Trafficking in Homeostatic Synaptic Plasticity: Functional Molecules and Signaling Cascades - Guan Wang; James Gilbert; Heng-Ye Man (Neural Plasticity)
Homeostatic synaptic plasticity is a negative-feedback response employed to compensate for functional disturbances in the nervous system. Typically, synaptic activity is strengthened when neuronal firing is chronically suppressed or weakened when neuronal activity is chronically elevated. At both the whole cell and entire network levels, activity manipulation leads to a global up- or downscaling of the transmission efficacy of all synapses. However, the homeostatic response can also be induced locally at subcellular regions or individual synapses. Homeostatic synaptic scaling is expressed mainly via the regulation of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) trafficking and synaptic expression. Here we review the recently identified functional molecules and signaling pathways that are involved in homeostatic plasticity, especially the homeostatic regulation of AMPAR localization at excitatory synapses.